THEMIS Observations of Particle Acceleration by a Magnetosheath Jet‐Driven Bow Wave - Terry Z. Liu; Heli Hietala; Vassilis Angelopoulos; Yuri Omelchenko; Vadim Roytershteyn; Rami Vainio (Geophysical Research Letters)
Abstract Localized magnetosheath jets with high dynamic pressure are frequently observed downstream of Earth's bow shock. When such a fast magnetosheath jet compresses the ambient magnetosheath plasma, an earthward compressional bow wave could form. Such bow waves have been predicted by simulations but have never been observed. Using multipoint Time History of Events and Macroscale Interactions during Substroms (THEMIS) observations, we report the first observation where such a bow wave driven by an intrinsically formed magnetosheath jet can reflect and accelerate particles up to tens of kiloelectron volt for ions and 100 keV for electrons. By analyzing the ion distributions, we infer how particles reach the spacecraft from the bow wave demonstrating good agreement with our model of single particle motion. Our study implies that particle acceleration at magnetosheath jets could contribute significantly to particle acceleration at shocks in general.